Evaluasi kasus meningioma di Rumah Sakit Wahidin Sudirohusodo Makassar tahun 2012-2018 - Djoko Widodo; Andi Ihwan; Mendila Purnamasari Arungpadang (Intisari Sains Medis, 2020)
Background: Meningioma is the most common tumor of the primary central nervous system (CNS) tumor, covering one-third or 36.4% of all tumors in the CNS. Some of the risk factors that are thought to be associated with meningioma include ionizing radiation, lifestyle, genetic factors, head trauma, and hormonal factors. However, until now, there are no factors that significantly and consistently have a direct relationship with the occurrence of meningioma. This study aimed to evaluate cases of meningioma at the Wahidin Sudirohusodo Hospital Makassar in 2012-2018.Methods: A cross-sectional study with a descriptive and retrospective approach was conducted from the medical records of neurosurgical patients treated at the Wahidin Sudirohusodo Hospital Makassar in 2012-2018. The variables assessed in this study included gender, age group, tumor location, and variations in meningioma pathology. Data were analyzed using SPSS version 17 for Windows.Results: Most of the study respondents were female (72.1%) than males (27.9%). The 51-60 year age group contributed to 32.4% of meningioma cases. The tumor's location was found most frequently in the parietal (29.4%) followed by the frontal (22.1%). Based on the variety of pathology, meningothelial meningioma was the most frequent case in Grade 1 (11.8%), followed by Atypical meningioma in Grade II (22.1%), and Anaplastic meningioma in Grade III (23.5%).Conclusion: Meningioma cases at Wahidin Sudirohusodo Hospital Makassar in 2012-2018 were partly female, age group 51-60 years, parietal location, and differences in pathological variations in each grade.  Latar Belakang: Meningioma merupakan tumor tersering dari tumor primer susunan saraf pusat (SSP) yang meliputi sepertiga atau 36,4 % dari seluruh tumor pada SSP. Beberapa faktor resiko yang diduga berhubungan dengan terjadinya meningioma meliputi radiasi ion, pola hidup, faktor genetik, trauma kepala, dan faktor hormonal. Akan tetapi, hingga saat ini belum ada faktor yang secara bermakna dan konsisten berhubungan langsung dengan terjadinya meningioma. Peneltiian ini bertujuan untuk mengevaluasi kasus meningioma di Rumah Sakit Wahidin Sudirohusodo Makassar tahun 2012-2018Metode: Penelitian ini bersifat potong lintang dengan pendekatan secara deskriptif dan retrospektif yang bersumber dari data rekam medis pasien bedah saraf yang dirawat di Rumah Sakit Wahidin Sudirohusodo Makassar tahun 2012-2018. Variabel yang dinilai pada penelitian ini meliputi Jenis kelamin, kelompok umur, lokasi tumor, dan variasi patologi meningioma. Data dianalisis dengan SPSS versi 17 untuk Windows.Hasil: Sebagian besar responden penelitian diketahui berjenis kelamin perempuan (72,1%) dibandingkan laki-laki (27,9%). Kelompok umur 51-60 tahun berkontribusi terhadap 32,4% kasus meningioma. Lokasi tumor ditemukan paling sering pada bagian parietal (29,4%) diikuti dengan bagian frontal (22,1%). Berdasarkan variasi patologi, Meningothelial Meningioma merupakan kasus yang paling sering pada Grade 1 (11,8%), diikuti dengan Atypical Meningioma pada Grade II (22,1%), dan Anaplastic meningioma pada Grade III (23,5%).Kesimpulan: Kasus meningioma di Rumah Sakit Wahidin Sudirohusodo Makassar tahun 2012-2018 sebagian berjenis kelamin perempuan, kelompok usia 51-60 tahun, lokasi parietal, dan perbedaan variasi patologi pada masing-masing Grade.